2018
DOI: 10.1001/jamapsychiatry.2018.1323
|View full text |Cite
|
Sign up to set email alerts
|

Association of Autistic Traits With Depression From Childhood to Age 18 Years

Abstract: Key PointsQuestionAre children with autism and autistic traits at greater risk of depression at age 18 years, and are genetic confounding and bullying important in these associations?FindingsAmong 6091 participants in this longitudinal study, children with autism and autistic traits had higher depressive symptom scores than the general population at age 10 years, remaining elevated in an upward trajectory until age 18 years. Social communication impairment was associated with depression at 18 years and was sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
129
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(139 citation statements)
references
References 44 publications
8
129
0
2
Order By: Relevance
“…A number of studies have compared prevalence rates of psychiatric disorders between youth with ASD and either the general population or typically developing youth. A large population-based longitudinal study included 6091 adolescents with and without ASD and examined the association with depression over eight years [ 23 ]. Using the Short Mood and Feelings Questionnaire (SMFQ) as the measure for depressive symptoms, adolescents with ASD had higher average scores when compared to the general population at age 10 years, and scores remained elevated in an upward trajectory until age 18 [ 24 ].…”
Section: Prevalencementioning
confidence: 99%
“…A number of studies have compared prevalence rates of psychiatric disorders between youth with ASD and either the general population or typically developing youth. A large population-based longitudinal study included 6091 adolescents with and without ASD and examined the association with depression over eight years [ 23 ]. Using the Short Mood and Feelings Questionnaire (SMFQ) as the measure for depressive symptoms, adolescents with ASD had higher average scores when compared to the general population at age 10 years, and scores remained elevated in an upward trajectory until age 18 [ 24 ].…”
Section: Prevalencementioning
confidence: 99%
“…In recent years, an increasing number of studies have assessed the association of bullying involvement with mental health problems in children and adolescents with ASD (12. A longitudinal study found that social communication impairments at the age of 10 years were associated with depression at the age of 18 years, and bullying victimization explained a substantial proportion of this risk (13). Parent-reported bullying victimization was significantly associated with anxiety symptoms in youth with ASD (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…9 The onset of depressive symptoms in autism appears to be early. A UK-based cohort study 10 reported that autistic children and children with higher autism traits have higher depressive symptoms at the age of 10 years and that these remain elevated with an upwards trajectory until the age of 18 years. Robust epidemiological research, particularly longitudinal studies, has been lacking until relatively recently.…”
Section: Introductionmentioning
confidence: 99%
“…Verbal abilities significantly influence the presentation or at least the identification of depression in this group. In addition, there is some evidence that better cognitive abilities and relatively low social impairment, 14 the tendency to make social comparisons 15 and a history of adverse experiences such as bullying 10 may be features of autistic young people with co-occurring depression.…”
Section: Introductionmentioning
confidence: 99%